Utilização de modelos de localização para dinamização do fluxo reverso de pneus inservíveis - Rocha, Bruno de Oliveira (2008)
This master thesis is about the use of location models for a system of reverse logistics of scap tires in the State of Ceará seeking the recycling of the rubber to be used in pavement asphaltic surfaces. A theoretical approach is accomplished regarding the management of scrap tires, especially on the recycling and reuse alternatives. It is analyzed the importance of the implantation ofRecycling Units, mainly in its benefit for the environment and for society. The description of the earnings involved in the incorporation of the tires recycled rubber in asphaltic mixtures is also approached, focusing the advantages offered by the asphalt-rubber. Aiming to achieve the objective proposed, it was considered the vehicle fleet of each city of the State as part of the methodology to medict the amount of scrap tires generated per year. In the conception of the models, it was analyzed the distances among cities, highway conditions of Ceará and other economical aspects (as the location of industrial poles). These factors led to define the city where the recycling factory must be installed and the prospective cities to receive the intermediate points of scrap tires storage (ecopoints). Based on the solution alternatives presented by the models, a proposalis suggested for the logistics of old tires reverse distribution, seeking itsincorporation in the asphaltic production chain. Finally, potential actions are identified to motivate the urban collection of tires at the local level.